2017
DOI: 10.1038/s41467-017-01141-y
|View full text |Cite
|
Sign up to set email alerts
|

Achieving high-efficiency emission depletion nanoscopy by employing cross relaxation in upconversion nanoparticles

Abstract: Stimulated emission depletion microscopy provides a powerful sub-diffraction imaging modality for life science studies. Conventionally, stimulated emission depletion requires a relatively high light intensity to obtain an adequate depletion efficiency through only light–matter interaction. Here we show efficient emission depletion for a class of lanthanide-doped upconversion nanoparticles with the assistance of interionic cross relaxation, which significantly lowers the laser intensity requirements of optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
238
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(249 citation statements)
references
References 67 publications
(80 reference statements)
4
238
1
Order By: Relevance
“…From microscopy to nanoscopy with breaking the optical diffraction limit, UC‐STED is an emerging technology enabling extensive development of the usage of the UCNPs for subcellular fine structure imaging. In 2017, Zhan et al demonstrated the first super‐resolution imaging of the cytoskeleton of HeLa cells with UCNPs . The synthesized 11.8 nm NaGdF 4 UCNPs were highly doped with Tm 3+ , up to 10 mol%, which enabled donut beam depletion of the emission light to gain super‐resolution imaging at blue wavelength.…”
Section: Nanoparticles For Microscopic Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…From microscopy to nanoscopy with breaking the optical diffraction limit, UC‐STED is an emerging technology enabling extensive development of the usage of the UCNPs for subcellular fine structure imaging. In 2017, Zhan et al demonstrated the first super‐resolution imaging of the cytoskeleton of HeLa cells with UCNPs . The synthesized 11.8 nm NaGdF 4 UCNPs were highly doped with Tm 3+ , up to 10 mol%, which enabled donut beam depletion of the emission light to gain super‐resolution imaging at blue wavelength.…”
Section: Nanoparticles For Microscopic Detectionmentioning
confidence: 99%
“…i–iv) Areas selected from (a) and (b) (marked by white dotted squares) and shown corresponding line profile analyses. Reproduced with permission . Copyright 2017, Macmillan Publishers Limited.…”
Section: Nanoparticles For Microscopic Detectionmentioning
confidence: 99%
“…reported that the blue upconversion emission at 455 nm of Tm 3 + ions in UCNPs doped with high concentrations of thulium ions, excited at a wavelength of 980 nm, can be optically inhibited by a laser at 808 nm . Interestingly, in an independent work we observed similar optical inhibition of the 455‐nm emission band of Tm 3 + ions (excited at 975 nm) by the addition of an 810‐nm laser irradiation in high Tm 3 + ‐doped UCNPs . Based on the advancement of optical depletion of upconversion luminescence, UCNPs have been used as probes for multi‐photon super‐resolution microscopy .…”
Section: Excitation Manipulation Of Upconversion Nanoparticlesmentioning
confidence: 63%
“…Based on the advancement of optical depletion of upconversion luminescence, UCNPs have been used as probes for multi‐photon super‐resolution microscopy . Particularly, we have implemented cytoskeleton protein super‐resolution imaging of immunolabeled HeLa cells using antibody‐conjugated UCNPs . UCNP‐mediated nanoscopy provides many advantages, including low laser intensity requirement, large penetration depth, non‐photobleaching and non‐photoblinking properties, cost‐effective and simplified imaging systems.…”
Section: Excitation Manipulation Of Upconversion Nanoparticlesmentioning
confidence: 99%
“…NaYF 4 nanocrystals, highly doped with ytterbium (Yb 3+ ) and thulium (Tm 3+ ) ions, have been used for STED imaging (Figure ) ,. These NPs can be excited and depleted using low‐power (<0.2 MW/cm 2 ) infrared laser beams by skillfully exploiting energy transfer processes between the ions.…”
Section: Nanoparticles For Super‐resolution Fluorescence Microscopymentioning
confidence: 99%